Bildung, Bedeutung und Gebrauch des russischen Verbalaspekts Teil 1: Theortische Grundlagen (Lehrbuch) - Schlegel, Hans (Specimina philologiae Slavicae, 2002)
Under the title "Education, Importance and Use of the Russian Verbal Aspect", a textbook is presented intended for advanced teaching at universities, colleges and high schools, for high-level, linguistically based self-education ("Autonomous Learning", better "autonomous study"), as well for teachers at colleges, language schools, high schools. This Part 1 contains the theoretical foundations - a didactic summary of the results of our work on the terminativity / aterativity of the Russian verb (Schlegel 1999) and the aspect-related reference moment (Schlegel 2001).